High-content method for mechanosignaling studies using IsoStretcher technology and quantitative Ca2+ imaging applied to Piezo1 in cardiac HL-1 cells - Merten, Anna-Lena; Schöler, Ulrike; Guo, Yang; Linsenmeier, Fabian; Martinac, Boris; Friedrich, Oliver; Schürmann, Sebastian (Cellular and Molecular Life Sciences, 2024)
The importance of mechanosensory transduction pathways in cellular signalling has prominently come to focus in the last decade with the discovery of the Piezo ion channel family. Mechanosignaling involving Piezo1 ion channels in the function of the heart and cardiovascular system has only recently been identified to have implications for cardiovascular physiology and pathophysiology, in particular for heart failure (i.e., hypertrophy or dilative cardiomyopathy). These results have emphasized the need for higher throughput methods to study single-cell cardiovascular mechanobiology with the aim of identifying new targets for therapeutic interventions and stimulating the development of new pharmacological agents. Here, we present a novel method to assess mechanosignaling in adherent cardiac cells (murine HL-1 cell line) using a combination of isotropic cell stretch application and simultaneous Ca2+ fluorescence readout with quantitative analysis. The procedure implements our IsoStretcher technology in conjunction with a single-cell- and population-based analysis of Ca2+ signalling by means of automated image registration, cell segmentation and analysis, followed by automated classification of single-cell responses. The method is particularly valuable for assessing the heterogeneity of populations with distinct cellular responses to mechanical stimulation and provides more user-independent unbiased drug response classifications.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Cardiomyocytes; Cell stretching; GsMTx4; Mechanobiology; Mechanosensitive; Mechanotransduction; Yoda1